2017
DOI: 10.1007/s10393-017-1254-9
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Disease Surveillance in the Woylie (Bettongia penicillata)

Abstract: Wild populations of the critically endangered woylie (Bettongia penicillata) recently declined by 90% in southwest Western Australia. Increased predation is the leading hypothesis for decline, but disease may be playing a role increasing susceptibility to predation. To explore this possibility, we surveyed woylie populations in the wild, in captivity and in a predator-free sanctuary for exposure to, and infection with, four known pathogens of macropods: herpesviruses, Wallal and Warrego orbiviruses, and Toxopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…The very low seroprevalence of T. gondii in B. penicillata (1.8%) is consistent with previous studies that used similar diagnostic methods (e.g. Parameswaran 2008;Skogvold et al 2017). Antemortem diagnosis of T. gondii, however, is difficult, given the often acute-onset and short-lived serological response to disease (Portas 2019).…”
Section: Mcinnessupporting
confidence: 87%
See 1 more Smart Citation
“…The very low seroprevalence of T. gondii in B. penicillata (1.8%) is consistent with previous studies that used similar diagnostic methods (e.g. Parameswaran 2008;Skogvold et al 2017). Antemortem diagnosis of T. gondii, however, is difficult, given the often acute-onset and short-lived serological response to disease (Portas 2019).…”
Section: Mcinnessupporting
confidence: 87%
“…The role of viruses has also been explored, though Pacioni et al (2014) found no evidence of exposure to viral pathogens in several B. penicillata populations, concluding that viral disease was an unlikely cause of the declines. While Skogvold et al (2017) subsequently detected herpesviruses in B. penicillata from Perup Sanctuary, infected hosts (n = 5) did not show signs of disease, thus the clinical significance of infection remains uncertain. The role of other parasites (e.g.…”
Section: Introductionmentioning
confidence: 99%